Relasi Kuasa dan Wacana Resistensi dalam Novel Janji Karya Tere Liye Perspektif Michel Foucault - Ramadani, Atika Suri; Satriani, Irma (Fakultas Sastra Universitas Muslim Indonesia, 2025)
This study aims to analyze the forms and dynamics of power relations in Tere Liye’s novel Janji through Michel Foucault’s theory of discourse and power. The research employs a qualitative method with a Foucauldian discourse analysis approach to examine how power operates, spreads, and produces truth within the novel’s social context. The data consist of textual excerpts that illustrate elements of surveillance, discipline, and resistance. The findings reveal that power in Janji is not monolithic or merely repressive but rather productive and diffused across three major domains: mental control through normalization and surveillance, bodily discipline through social and institutional mechanisms, and social domination maintained through economic and symbolic power. On the other hand, acts of resistance emerge as counter-discourses performed by the main character, demonstrating that power always allows space for opposition and social transformation. The study concludes that Janji reflects the complexity of power relations that not only constrain but also shape individual identity, behavior, and awareness within social networks, emphasizing the importance of critical consciousness toward the mechanisms of power embedded in everyday life.